Water-soluble diphosphine ligands for rhodium-catalyzed branch-selective hydroaminomethylation of vinyl arenes with anilines in water. Issue 11 (24th May 2022) - Zhang, Luyun; Ning, Yingtang; Ye, Baijun; Ru, Tong; Chen, Fen-Er
Abstract : Rhodium-catalyzed hydroaminomethylation of various vinyl arenes with anilines has been accomplished using water as an environmentally benign reaction media. Abstract : Rhodium-catalyzed hydroaminomethylation of various vinyl arenes with anilines has been accomplished using water as an environmentally benign reaction media. This aqueous reaction is facilitated by the water-soluble diphosphine ligands derived from bis(2-(diphenylphosphaneyl)ethyl)amides. The methodology demonstrated a broad scope of substrates and accessed the N -(2-phenylpropyl)anilines in good yields (up to 94%) and high selectivities. Mechanistic studies with a series of competition experiments and isotope labeling revealed the imine hydrogenation reactivity of the catalysts.